234 Congress Street, ca. 1895 - Unknown (Tufts Archival Research Center, 2005)
Street-level view north of 234 Congress Street, located at the northeast corner of Congress and Purchase Streets. Signage adorns the southwest corner and facade of the building, which faces southwest towards Congress Street. A man stands on the sidewalk near a horse and sleigh in front of the building. Copyprint 9 1/8 x 7 1/8 Photographs